Increased peritoneal TGF-β1 is associated with ascites-induced NK-cell dysfunction and reduced survival in high-grade epithelial ovarian cancer - Maas, Ralph J. A.; Hoogstad-van Evert, Janneke S.; Hagemans, Iris M.; Brummelman, Jolanda; van Ens, Diede; de Jonge, Paul K. J. D.; Hooijmaijers, Laura; Mahajan, Shweta; van der Waart, Anniek B.; Hermans, Charlotte K. J. C.; de Klein, Janne; Woestenenk, Rob; et al. (Frontiers in Immunology, 2024)
Natural killer (NK) cell therapy represents an attractive immunotherapy approach against recurrent epithelial ovarian cancer (EOC), as EOC is sensitive to NK cell-mediated cytotoxicity. However, NK cell antitumor activity is dampened by suppressive factors in EOC patient ascites. Here, we integrated functional assays, soluble factor analysis, high-dimensional flow cytometry cellular component data and clinical parameters of advanced EOC patients to study the mechanisms of ascites-induced inhibition of NK cells. Using a suppression assay, we found that ascites from EOC patients strongly inhibits peripheral blood-derived NK cells and CD34+ progenitor-derived NK cells, albeit the latter were more resistant. Interestingly, we found that higher ascites-induced NK cell inhibition correlated with reduced progression-free and overall survival in EOC patients. Furthermore, we identified transforming growth factor (TGF)-β1 to correlate with ascites-induced NK cell dysfunction and reduced patient survival. In functional assays, we showed that proliferation and anti-tumor reactivity of CD34+ progenitor-derived NK cells are significantly affected by TGF-β1 exposure. Moreover, inhibition of TGF-β1 signalling with galunisertib partly restored NK cell functionality in some donors. For the cellular components, we showed that the secretome is associated with a different composition of CD45+ cells between ascites of EOC and benign reference samples with higher proportions of macrophages in the EOC patient samples. Furthermore, we revealed that higher TGF-β1 levels are associated with the presence of M2-like macrophages, B cell populations and T-regulatory cells in EOC patient ascites. These findings reveal that targeting TGF-β1 signalling could increase NK cell immune responses in high-grade EOC patients.